(untitled) (Mongolian Journal of Agricultural Sciences, 2025)
We carefully filtered all the studies on the classification of Tettigonoidea distributed in Mongolia, since 1960s and combined with our research results. As a result we found that 42 species (17 subspecies), 3 subtribes, 6 tribes, 16 genera, 2 subspecies belonging to 1 superfamily, were recorded in Mongolia. As a result of field research, 392 samples were collected from 140 points of 116 sums in 18 provinces of Mongolia. Deracantha onos Pallas, 1772 (Common bull katydid) has been determined to be Mongolia’s most widespread katydid species. As a result of our field research conducted in 2013-2022, 82 out of 43 research points in 31 districts of 12 provinces were found. It was determined and consolidated. Based on this distribution map, using the Maxent-Geographic distribution model, it was calculated that the Common bull katydid is spread over an area of 881,730 km2. It is estimated that the average annual temperature will increase by 2.2 degrees and precipitation by 14.5 percent in 2050. In the year 2080, the Maxent model predicts that the distribution of the will increase slightly from the current average annual temperature of 4.0 degrees, and precipitation will increase by 25.8 percent.